Focus group: mixed Hutu community (adults, young people and the elderly) (Uhamaji wa wanyerwanda: Migration and Conflict in Ituri, DR Congo, 2020)
This is the translation of a focus group interview
Keywords: Land tenure; Migration; Social conflict; Conflict Theory